De-Mystifying Translation : Introducing Translation to Non-Translators. - Bowker, Lynne. (Taylor & Francis Group, 2023)
This textbook provides an accessible introduction to the field of translation for students of other disciplines and readers who are not translators. It provides students outside the translation profession with a greater awareness of and appreciation for what goes into translation.